When students show some initiative: Two experiments on the benefits of greater agentic engagement. (August 2022) - Reeve, Johnmarshall; Jang, Hye-Ryen; Shin, Stephanie Hyewon; Ahn, Jiseul Sophia; Matos, Lennia; Gargurevich, Rafael
Abstract: Correlational and longitudinal research suggests that agentically-engaged students experience multiple educational benefits. Recognizing this, two experiments tested the causal capacity of manipulated agentic engagement to create three categories of benefits: a supportive learning environment; motivational satisfactions; and effective functioning (e.g., engagement, performance). Study 1 used the teacher–student laboratory paradigm to place 121 same-sex pairs of preservice teachers into the roles of teacher and student during a videotaped 12-min instructional episode. Teachers were randomly assigned to be autonomy supportive or not, while students were randomly assigned to be agentically engaged or not. MANOVAs on 10 self-reported and rater-scored dependent measures showed that manipulated agentic engagement enhanced both a supportive learning environment and greater motivational satisfaction but not more effective functioning. Study 2 used the same teacher-student paradigm to randomly assign 74 same-sex pairs into one of three conditions: agentic engagement to change the environment (as in Study 1); agentic engagement to change one's functioning (a new Study 2 manipulation); and a neutral control. The first manipulation again enhanced the supportive learning environment and motivational satisfaction but not effective functioning, while the second manipulation produced no benefits. Collectively, these findings confirm some limited causal benefits from agentic engagement and therefore provide guidance for future research, including the design and implementation of student-focused agentic engagement interventions. Highlights: Manipulated agentic engagement produced multiple educational benefits. In two experiments, the effect of greater agency on these benefits was causal. These findings lay the groundwork for future student-focused agentic engagement interventions.